Chancroid – desperate patient makes own diagnosis. (September 2014) - Barnes, P; Chauhan, M
We report a case of chancroid in a white heterosexual man in the United Kingdom. This patient was seen by four separate health services over a period of five weeks with excruciatingly painful penile ulcers. Despite several negative herpes simplex virus polymerase chain reaction tests and a self-diagnosis of chancroid, he was repeatedly offered multiple courses of aciclovir. This case highlights the need for awareness of alternative diagnoses in persistent cases of genital ulcer disease.